RANCANG BANGUN KOPER SMART GESTURE BERBASIS ARDUINO - Safwan; Feri susilawati; Dedi Munandar; Fitriady (Politeknik Aceh, 2019)
Smart Gesture is one of the interesting technologies to be developed. Smart gesture can be harnessed into a vast range of things to ease the people work people. In general the suitcase uses to pack the stuff which is pulled manual. By using a Smart Gestures suitcase, user does not need to pull the trunk anymore, it can be controlled by using gloves. Smart Gesture is applied on a suitcase using the accelerometer sensor to start the motor. It controls the suitcase on the level of the slope of the hands resulting from the accelerometer sensor. To minimize the discharge of excess power in pulling the suitcase, it makes the user to control the suitcase without pulling it directly.